Evaluation of the anti-viral activity of nanoparticles on HSV-1 virus - Sana Al Attas (International Journal of Pharma and Bio Sciences, 2021)
In the present study, the antiviral potential of various nanoparticles was evaluated, such as BiOCI, Nickel Oxide (NiO), Calcium carbonate (CaCO3), MgZO24, and Magnesium hydroxide (Mg (OH)2). The antiviral effect of these nanoparticles was evaluated on the Herpes Simplex virus-1 (HSV-1) virus. The antiviral potential of various nanoparticles have been evaluated, such as Bioci Bismuth Oxychloride, Nickel Oxide (NiO), Calcium carbonate (CaCO3), MgZO 24 Magnesium Zink Oxide, and Magnesium hydroxide (Mg (OH)2). The antiviral effect of these nanoparticles was evaluated on the Herpes Simplex virus-1 (HSV-1) virus. The maximum non-toxic dose of nanoparticles was found to be 100 μg/ml, and this concentration was used to analyze their antiviral effects. None of the tested nanoparticles exhibited significant HSV-1 inhibition in the cell-based assay and MTT assay. However, in the Plaque assay, some inhibition of viral activity was seen in the case of NiO and CaCO3 nanoparticles as compared to virus control. This antiviral activity was similar to the positive control of usnic acid, used in this study. Since these nanoparticles did not show any significant anti-viral activity in MTT assay, the activity of these compounds, i.e., NiO and CaCO3 nanoparticles needs to be further confirmed by using higher doses of these compounds, and also further optimization of the anti-viral essay is required in order to achieve the significant antiviral activity.